Distributed National Collections: Concept and Reality in Two Countries - Genoni, Paul (2002)
This paper examines the prospects for the successful implementation of a distributed national collec-tion policy in the United Kingdom. It does so by tracing the Australian experience with the implemen-tation of a similar scheme, the Distributed National Collection (DNC), during the late 1980s and 1990s. The rationale for the introduction of the DNC is explained, and some of the reasons for its per-ceived failure are examined. The paper then traces the recent development of a similar proposal in the UK, and discusses the differences between the Australian and UK contexts for the introduction of such an approach to collaborative collection building. It concludes that these differences give some cause for optimism that the UK push for a coordinated and formalized approach to collecting print material on a national scale may be more successful, while pointing to the key challenges ahead.